ANTIBACTERIAL ACTIVITY OF GREEN SEAWEEDS CHAETOMORPHA AND ENTEROMORPHA - MEGHA N. MOLE; ANJALI B. SABALE (International Journal of Pharma and Bio Sciences, 2013)
Antibacterial activities of two green seaweeds, namely Chaetomorpha media (C. Agardh) Kutz. and Enteromorpha intestinalis (L.) Nees were screened against five common human bacterial pathogens (Escherichia coli, Proteus vulgaris, Bacillus subtilis, Salmonella typhi and Staphylococcus aureus).Extracts of dry algal material, prepared in Methanol, Ethanol, Petroleum ether, Ethyl acetate and Hexane were tested for the antibacterial activity. Ethanol extract of both the algae was found effective against all the bacterial strains used. Maximum inhibition was reported for the ethanol extracted E. intestinalis (87.50%) and methanol extracted C. media (84.70%) against bacterium Proteus vulgaris. E. coli was found to be the most insensitive pathogen in the present study and exhibited 40–50% inhibition in different solvents.